Proficient communication between sensor devices using heuristic approaches in IoT environment. (2018) - Ramachandran, Nandhakumar; Perumal, Varalakshmi
The proposed system comprises of dynamic and heterogeneous sensors in internet of things (IoT) environment and aims at achieving an efficient communication among sensor devices by choosing the most optimal nodes at every stage of the communication. The base station releases a query, according to which clustering is done with their Cluster Heads using particle swarm optimisation (PSO), which is based on factors like position, velocity, energy and the neighbour density. Principle component analysis is used at relay node to aggregate heterogeneous data of multiple dimensions. It reduces the dimensionality of data sent thus reducing the packets sent. Ant colony optimisation (ACO) is used to forward data at every level by considering the energy of the node, distance from base station and the velocity. The technique helps in choosing reliable, energy efficient path and also decreases the delay. Thus, the proposed system is used in overcoming the resource constraint problem, this in turn improves the network lifetime.